2015
DOI: 10.3332/ecancer.2015.526
|View full text |Cite
|
Sign up to set email alerts
|

The role of human papillomaviruses in carcinogenesis

Abstract: The human papillomavirus (HPV) family comprises more than 170 different types that preferentially infect the mucosa of the genitals, upper-respiratory tract, or the skin. The ‘high-risk HPV type’, a sub-group of mucosal HPVs, is the cause of approximately 5% of all human cancers, which corresponds to one-third of all virus-induced tumours. Within the high-risk group, HPV16 is the most oncogenic type, being responsible for approximatively 50% of all worldwide cervical cancers. Many studies suggest that, in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
1
10

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 60 publications
1
144
1
10
Order By: Relevance
“…As a result even after the vaccination, the tendency for patients to be infected with other strains still exists. Hence, both bivalent and quadrivalent do not cover 20-30% of HPV-associated cancers (17) . …”
Section: Vaccines Against Other Hpv Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result even after the vaccination, the tendency for patients to be infected with other strains still exists. Hence, both bivalent and quadrivalent do not cover 20-30% of HPV-associated cancers (17) . …”
Section: Vaccines Against Other Hpv Typesmentioning
confidence: 99%
“…The support of government funding to make HPV vaccines as national health program is crucial, although, in reality, it is a difficult decision (31) . Cost is one of the major barriers in reducing cervical cancer, in the USA a survey was done in 2008 found that only 12% among female adolescents aged [11][12][13][14][15][16][17] To who had no health insurance received HPV vaccination (32) . This shows that public is not willing to pay to get vaccinated.…”
Section: Cost and Affordabilitymentioning
confidence: 99%
“…Although this virus exists in over 170 variants, and several of them cause cancer, there are none to very few sequences of some of the important variants available in the NIH GenBank database. Although available vaccines against the primary types of this dsDNA (double-stranded DNA) virus have proved very effective, they leave out 20-30% of the cases [30] and continue to be very expensive, often beyond the capacity of affordability of a vast swathe of human population. It is possible that adequate data are available but are being held back for unexplained reasons, but lack of such data hinders intensive analyses and prolongs the sufferings of a large section of humanity.…”
Section: Rational Design Of Peptide Vaccines Against the Zika Virus Tmentioning
confidence: 99%
“…High-risk HPV types, such as HPV 16, 18, 31, 33, and 35, are mostly associated with cancer (5). HPV 16 and 18 are the most prevalent types reported worldwide, contributing to approximately 70% of cervical cancers, while other high-risk HPV genotypes are associated with more than 20% of cervical cancers globally (3,6).…”
Section: Introductionmentioning
confidence: 99%